Feeding practices among under two years children in urban slum, Bengaluru: a cross sectional study - Hamsa L.; N. G., Pradeep Kumar; Ranganath T. S. (International Journal Of Community Medicine And Public Health, 2023)
Background: Exclusive breastfeeding is the optimum method of feeding in first 6 months of life. It meets nutritional requirement of baby. There are practices of early introduction of top feeds and late introduction of semi-solid feed in urban slums in India. This study was conducted to assess feeding practices among under 2 years children in an urban slum area. Methods: A community based cross sectional study was conducted in one of the urban slums in Bengaluru among 190 caregivers of children aged from 6 months to 2 years from January 2023 to March 2023. Questionnaire was used to collect information regarding feeding practices and data was analysed using JAMOVI v2.3.26. Results: Among 155 (81.58%) of the mothers were literates, 97 (51.06%) belongs to class IV socioeconomic status. Regarding feeding practices, 65 (34.21%) of them initiated breastfeeding between 1-4 hours after delivery, 137 (72.11%) of them fed colostrum to the babies, pre-lacteal feeds were given in 46 (24.21%) of children, exclusive breastfeeding was done in 106 (55.79%) of babies. There was significant association between exclusive breastfeeding with caregivers’ socioeconomic status, type of family (p<0.05). There was significant association between pre-lacteal feeds with mothers’ education status, socio-economic status (p<0.05). Conclusions: There is a need for health education regarding importance of exclusive breastfeeding and ill-effects of pre-lacteal feeds. Sociodemographic factors also play an important role in these feeding practices. Hence government should take necessary steps to improve some of the demographic factors who are living in urban slums.